Transcriptional expression of Toll-like receptors and proinflammatory cytokines in macrophages infected with native Leishmania braziliensis - Torres Gonzales, Dina (2024)
Introduction. The Toll-like receptor (TLR) interacting with the promastigote of Leishmania spp. determines the cellular activation pathway. Objective. To determine the transcriptional expression of TLR-3, TLR-4, TLR-9, IL-12 and TNF-α in macrophages infected with a native strain of L. braziliensis (Lbn). Materials and Methods. Identification of Lbn was performed by qPCR for kinetoplast DNA sequences. Mouse peritoneal macrophages were infected with promastigotes (MI) and nitric oxide (NO) production was measured; transcript levels for TLRs and cytokines were quantified by qRT-PCR. Results. Lbn showed 96% homology to L. braziliensis. High ON production was observed in IMs at 2 h; significant transcriptional expression especially of TLR-3 and TLR-9, which corresponded with expression for cytokines. Conclusions. Lbn strongly activated macrophages via endosomal TLRs, which can be applied in the design of agonists to treat the disease.